Colony-stimulating factor (CSF) 1 receptor blockade reduces inflammation in human and murine models of rheumatoid arthritis. Issue 1 (December 2016) - Garcia, Samuel; Hartkamp, Linda; Malvar-Fernandez, B; van Es, Inge; Lin, Haishan; Wong, Justin; Long, Li; Zanghi, James; Rankin, Andrew; Masteller, Emma; Wong, Brian; Radstake, Timothy; et al.
Abstract Background CSF-1 or IL-34 stimulation of CSF1R promotes macrophage differentiation, activation and osteoclastogenesis, and pharmacological inhibition of CSF1R is beneficial in animal models of arthritis. The objective of this study was to determine the relative contributions of CSF-1 and IL-34 signaling to CSF1R in RA. Methods CSF-1 and IL-34 were detected by immunohistochemical and digital image analysis in synovial tissue from 15 biological-naïve rheumatoid arthritis (RA), 15 psoriatic arthritis (PsA) and 7 osteoarthritis (OA) patients . Gene expression in CSF-1- and IL-34-differentiated human macrophages was assessed by FACS analysis and quantitative PCR. RA synovial explants were incubated with CSF-1, IL-34, control antibody (Ab), or neutralizing/blocking Abs targeting CSF-1, IL-34, or CSF1R. The effect of a CSF1R-blocking Ab was examined in murine collagen-induced arthritis (CIA). Results CSF-1 (also known as M-CSF) and IL-34 expression was similar in RA and PsA synovial tissue, but lower in controls (P < 0.05). CSF-1 expression was observed in the synovial sublining, and IL-34 in the sublining and the intimal lining layer. CSF-1 and IL-34 differentially regulated the expression of 17 of 336 inflammation-associated genes in macrophages, including chemokines, extra-cellular matrix components, and matrix metalloproteinases. Exogenous CSF-1 or IL-34, or their independent neutralization, had no effect on RA synovial explant IL-6 production. Anti-CSF1R Ab significantly reduced IL-6 and other inflammatory mediator production in RA synovial explants, and paw swelling and joint destruction in CIA. Conclusions Simultaneous inhibition of CSF1R interactions with both CSF-1 and IL-34 suppresses inflammatory activation of RA synovial tissue and pathology in CIA, suggesting a novel therapeutic strategy for RA.